The money school : 12 simple lessons to master financial markets and investing - Lapin, Nicole (HarperCollins Leadership, an imprint of HarperCollins, 2025)
Realize financial stability and investing confidence with this one-of-a-kind resource by renowned money expert Nicole Lapin. She gets into the nitty gritty of stocks and bonds, touching on how people talk about them and how they can invest in them as part of their investment portfolio.--